The Impact of Big Data on Accounting and Auditing - D. Balios (International Journal of Corporate Finance and Accounting)
Big data and big data analytics will unavoidably change the role of accountants. This paper considers the impact of big data on accounting and auditing. Financial accountants need to move beyond the book-keeping process and become key information providers to decision-makers. That upturns accountants’ consulting role and their ability to think strategically, providing critical help in management decision making. The relationship between managers and management accountants becomes closer and more effective because of big data. Management accountants can use additional analytical methods to detect processes and product excellence, combined with diminishing cost. Big data and big data analytics in auditing ensure audit quality and fraud detection. Upgraded information systems and automation in business procedures diminish the need for staff participation. Inevitably, the skills of accountants and knowledge must be associated with big data and big data analytics and modern accountants must develop an analytics mindset by being familiar with data and technologies.